The Use of Gadgets on Parenting Patterns in the Digital Era - Maya Paschalia (CV. Media Inti Teknologi, 2025)
This study aims to determine the parenting patterns of parents towards the use of gadgets in the digital era. The development of the era, especially gadgets, has a very rapid impact, one of which is on child development. Gadgets can affect child development such as the time and content presented. This study uses a quantitative approach. The sample was 10 children in Lavender class, Kindergarten, Gembala Baik, aged 5-6 years. Based on the assessment, the average results of the parenting patterns applied by parents were a mean of 16, a median of 16, and a standard deviation of 3.1. This assessment has a score of 1 to a maximum of 5 for each question. The results of the study showed that there was a score of 11 and a score of 21. So it can be concluded that parenting patterns in this digital era are good, especially in the use of gadgets. Parents supervise and limit the use of gadgets in children so that time and content can be controlled properly. The importance of supervising the content presented and limiting the time in using gadgets in children so that the use of technology in the digital era is more effective and efficient.